Valorization of coffee grounds for biodiesel production - Nídia S.Caetano (2012)
This work evaluates the use of spent coffee grounds (SCG) for biodiesel production. The SCG were characterized for their moisture content (12.1 wt%), total carbon (TC) and total nitrogen (TN) (52.2 and 2.1 wt% respectively), cellulose and total lignin contents (33.6 wt% and 13.8 wt% respectively), carbon/nitrogen mass ratio (C/N = 24.8) and higher heating value (HHV, of 19.3 MJ/kg). For extracting the oil from the SCG, several solvents were tested at different contact times: hexane, ethanol, isopropanol, heptane and a mixture of hexane/isopropanol in the proportions of 50:50; 60:40; 70:30 and 80:20 (vol/vol). Results revealed an oil content ranging from 6.3 to 28.3 wt%, depending on the extraction conditions. For example, using hexane/isopropanol (50:50, vol/vol) a 21.5 wt% of oil recovery was obtained after 3 h of contact time, while using isopropanol a 21.0 wt% of oil recovery was obtained in 6.8 h, but at higher operating cost, considering the energy and solvent consumption. Regarding the oil characterization the following parameters can be highlighted: HHV of 36.4 MJ/kg, iodine value of 54.4 (g I2)/(100 g oil), water content of 2004 ppm and acid value of 118.4 (mg KOH)/(g oil). Finally, the possibility of using the recovered coffee oil for biodiesel production was evaluated. In this regard it was performed the oil esterification in three consecutive steps (using 1% of H2SO4 and 40 % of methanol for 2 h of reaction time at 60 ºC and 500 rpm) followed by one transesterification step (1 % of NaOH and 40 % of methanol during a 2 h reaction time at 60 ºC and 500 rpm). The resulting biodiesel was characterized for its acid value, density, viscosity at 40 ºC, iodine value and esters content (65.7 to 72.9 %), of which only the iodine value of 26 and 58.4 (g I2)/(100 g biodiesel) was within the NP EN14214:2009 standard limits. The reaction yield varied between 58.8 and 62.2 wt%. Results suggest the need for a further process optimization in order to obtain a biodiesel complying with this standard quality requirements.